IMPLEMENTING ICT IN FOREIGN LANGUAGE LEARNING AND TEACHING: IMPLEMENTING ICT IN FOREIGN LANGUAGE LEARNING AND TEACHING - Dauletmuratova, Khurziya (Журнал иностранных языков и лингвистики, 2021)
This paper deals with the role of technology and using it effectively for language teaching and learning, investigating some of the educational apps that can boost this process and make the lessons interesting than traditional ways of method, and increasing to momentous enhancement in teacher and student attitudes toward and confidence with ICT. Additionally, the technology in learning and teaching process is essential in order to improve the knowledge and skills of learners, prompt student motivation as well.